Characterization of MADS homeotic genes in the fern Ceratopteris richardii - Hasebe, Mitsuyasu (The National Academy of Sciences, 1998)
The MADS genes encode a family of transcription factors, some of which control the identities of floral organs in flowering plants. To understand the role of MADS genes in the evolution of floral organs, five MADS genes (CMADS1, 2, 3, 4, and 6) were cloned from the fern Ceratopteris richardii, a nonflowering plant. A gene tree of partial amino acid sequences of seed plant and fern MADS genes showed that the fern genes form three subfamilies. All members of one of the fern MADS subfamilies have additional amino-terminal amino acids, which is a synapomorphic character of the AGAMOUS subfamily of the flowering plant MADS genes. Their structural similarity indicates a sister relationship between the two subfamilies. The temporal and spatial patterns of expression of the five fern MADS genes were assessed by Northern blot analyses and in situ hybridizations. CMADS1, 2, 3, and 4 are expressed similarly in the meristematic regions and primordia of sporophyte shoots and roots, as well as in reproductive structures, including sporophylls and sporangial initials, although the amount of expression in each tissue is different in each gene. CMADS6 is expressed in gametophytic tissues but not in sporophytic tissues. The lack of organ-specific expression of MADS genes in the reproductive structures of the fern sporophyte may indicate that the restriction of MADS gene expression to specific reproductive organs and the specialization of MADS gene functions as homeotic selector genes in the flowering plant lineage were important in floral organ evolution.